Leveraging Heuristic Approaches to Optimize Lattice-Based Homomorphic Encryption via Approximate Shortest Vector Problem Solutions - Biswas, Lisa (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
Lattice-based cryptography is becoming a key part of secure communication that can protect information even from powerful quantum computers, especially when it comes to fully homomorphic encryption, which allows data to be processed without being decrypted. This paper tries to explore the application of heuristic methods to approximate solutions to the Approximate Shortest Vector Problem (Approx-SVP), which could help improve the speed of certain secure encryption systems that rely on lattice-based cryptography. Given the computational intensity of Approx-SVP, the study aims to develop tailored heuristic techniques that improve efficiency. This paper focuses on simulation experiments and theoretical analyses to evaluate performance metrics. The inference from the findings indicates significant improvements which pave the way for exploring how optimizations might affect the security considerations of lattice- based cryptography in practical cryptographic systems.